High-Performance Chip Design with Parallel Architecture for Magnetic Field Imaging System - Lin, Ming-Yi; Hsieh, Sheng-Hsien; Chen, Ching-Han; Lin, Chun-Hung (IEEE transactions on instrumentation and measurement, 2024)
To address the limitations of typical coil detection systems and enhance the performance of traditional magnetic field imaging systems, we propose a magnetic field imaging system that uses a 4 × 4 array of anisotropic magnetoresistance (AMR) sensors. The core controller of the proposed system was designed using a pipelined parallelization algorithm and implemented on a high-speed field-programmable gate array in a fully hardware-based architecture. The designed magnetic field imaging system can achieve parallel acquisition of magnetic field components from the 16-channel AMR sensor array, parallel data processing, parallel data transmission, and parallel computations in a single cycle of only 4 ms. Compared with typical detection systems, the proposed solution not only exhibits superior performance but can also provide dynamic visual representations of sensed information.